(untitled) (Research, Society and Development, 2024)
Introduction: Population aging is a natural and global phenomenon, requiring better access opportunities for the elderly in social, cultural, physical, and psychological areas. Objectives: This study aims to estimate the prevalence of psychological problems and violence among the elderly in Araguari-MG and compare the impacts of these conditions concerning adverse effects. Methodology: An observational, analytical, cross-sectional, and quantitative methodology was used, with a random sample of 376 elderly individuals analyzed through semi-structured questionnaires. Results: The research indicated a high prevalence of anxiety (24.3%) and depression (14.1%), with significant associations between these disorders and adverse events such as insomnia and sensory impairments. Domestic violence was identified in 2.5% of cases, revealing the need for interventions focused on the mental health and well-being of the elderly. Conclusion: The study concludes that there is an urgent need for comprehensive public policies and a multifactorial approach, guided by the principles of the Brazilian Unified Health System (SUS), to promote aging with quality of life.